Load bearing capacity of stainless steel beams at elevated temperatures - Alves, Matheus Henrique (2022)
To analyse the load bearing capacity of stainless steel (SS) members at elevated temperatures, a set of three-point bending tests was conducted on RHS 150x100x5 beams with SS grade 1.4301. The numerical modelling of these tests has been performed at elevated temperatures, achieving close approximation to observed experimental results. The load bearing capacity difference between the numerical results and the experimental results is smaller than 10%. Analytical methods were also used to predict the load-deflection behaviour.